Quantum Mechanics A Modern and Concise Introductory Course - Bes, Daniel; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
Starting from basic principles, the book covers a wide variety of topics, ranging from Heisenberg, Schroedinger, second quantization, density matrix and path integral formulations of quantum mechanics, to applications that are (or will be) corner stones of present and future technologies. The emphasis is on spin waves, quantum information, recent tests of quantum physics and decoherence. The book provides a large amount of information without unbalancing the flow of the main ideas by laborious detail.
Introduction -- The Principles of Quantum Mechanics -- Other Consequences of the Basic Principles -- The Heisenberg Realization of Quantum -- The Schroedinger Realization of Quantum Physics -- Angular Momenta -- Three-Dimensional Hamiltonian -- Many-Body Problems -- Approximate Solutions to Quantum Problems -- Time-Dependence in Quantum Mechanics -- Broken Symmetries -- Entanglement and Experimental Tests of Quantum Mechanics -- Quantum Information -- Other Formulations of Quantum Mechanics: the Density Matrix and the Path Integral -- The Classical and Quantum Realities. Decoherence and Measurements -- A Brief History of Quantum Mechanics.
Keywords: Quantum physics; Quantum field theory; String theory; Quantum Physics; Quantum Field Theories, String Theory